The effect of oxygen plasma ashing on the resistance of TiN bottom electrode for phase change memory*Project supported by the National Key Basic Research Program of China (Nos. 2010CB934300, 2013CBA01900, 2011CBA00607, 2011CB932804), the Strategic Priority Research Program of the Chinese Academy of Sciences (No. XDA09020402), the National Integrate Circuit Research Program of China (No. 2009ZX02023-003), the National Natural Science Foundation of China (Nos. 61176122, 61106001, 61261160500, 61376006), and the Science and Technology Council of Shanghai (Nos. 12nm0503701, 13DZ2295700, 12QA1403900, 13ZR1447200). (May 2015) - Gao, Dan; Liu, Bo; Li, Ying; Song, Zhitang; Ren, Wanchun; Li, Juntao; Xu, Zhen; Lü, Shilong; Zhu, Nanfei; Ren, Jiadong; Zhan, Yipeng; Wu, Hanming; et al.
Abstract Phase change memory (PCM) has been regarded as a promising candidate for the next generation of nonvolatile memory. To decrease the power required to reset the PCM cell, titanium nitride (TiN) is preferred to be used as the bottom electrode of PCM due to its low thermal and suitable electrical conductivity. However, during the manufacture of PCM cell in 40 nm process node, abnormally high and discrete distribution of the resistance of TiN bottom electrode was found, which might be induced by the surface oxidation of TiN bottom electrode during the photoresist ashing process by oxygen plasma. In this work, we have studied the oxidation of TiN and found that with the increasing oxygen plasma ashing time, the thickness of the TiO2 layer became thicker and the state of the TiO2 layer changed from amorphous to crystalline, respectively. The resistance of TiN electrode contact chain with 4-5 nm TiO2 layer was confirmed to be almost three-orders of magnitude higher than that of pure TiN electrode, which led to the failure issue of PCM cell. We efficiently removed the oxidation TiO2 layer by a chemical mechanical polishing (CMP) process, and we eventually recovered the resistance of TiN bottom electrode from 1 × 105 Ω/via back to 6 × 102 Ω/via and successfully achieved a uniform resistance distribution of the TiN bottom electrode.